Defining Functionally Relevant Spatial Chromatin Domains: It is a TAD Complicated. Issue 3 (7th February 2020) - Sikorska, Natalia; Sexton, Tom
Abstract: Chromosome conformation capture and orthologous methods uncovered the spatial organization of metazoan chromosomes into autonomously folded substructures, often termed topologically associated domains (TADs). There is a striking correlation between TAD organization and hallmarks of genome function, such as histone modifications or gene expression, and disruptions of specific TAD structures have been associated with pathological misexpression of underlying genes. However, complete disruption of TADs seems to have mild effects on the transcriptome, raising questions as to the importance of chromatin topology in regulating the expression of most genes. Furthermore, despite a growing number of genetic perturbation studies, it is still largely unclear how TAD-like domains are defined, maintained, or potentially reorganized. This perspective article discusses the recent work exploring the complexity of the relationship between TADs and transcription, arguing that it is not satisfactorily explained by any of the "rules" that have been previously described. Graphical abstract: Image 1 Highlights: Complex, context-dependent link between TAD organization and transcription. Convergent CTCF motifs are not sufficient for all TAD formation. More case studies are required to refine global perturbation studies of TADs.